Barcoding of Asian seabass across its geographic range provides evidence for its bifurcation into two distinct species - Vij, Shubha; Purushothaman, Kathiresan; Gopikrishna, G.; Lau, Doreen; Saju, Jolly M.; Shamsudheen, K. V.; Kumar, K. Vinaya; Basheer, V. S.; Gopalakrishnan, A.; Hossain, Mohammad S.; Sivasubbu, Sridhar; Scaria, Vinod; et al. (Frontiers in Marine Science, 2014)
Asian seabass or barramundi (Lates calcarifer) is an important food fish with commercial value and a wide geographic distribution. Though some reports based on molecular and/or morphological data exist, a comprehensive effort to establish species identity across its range is lacking. In order to address this issue and especially to ascertain whether the wide-spread distribution has resulted in bifurcation of the species, we collected Asian seabass samples from various locations representing the Western and Eastern Coastline of India, Andaman and Nicobar Islands, Bangladesh and Australia. Samples from Malaysia, Indonesia, Thailand and Singapore were collected as part of a previous study. DNA sequence variations, including cytochrome c oxidase subunit 1 (COI), 16S rDNA and the highly variable D-loop (or control region), were examined to establish species delineation. Data from all the sequences analyzed concordantly point to the existence of at least two distinct species - one representing the Indian subcontinent plus Myanmar, and a second, representing Southeast Asia (Singapore, Malaysia, Thailand and Indonesia) plus Northern Australia. These data are useful for conservation ecology, aquaculture management, for establishing the extent of genetic diversity in the Asian seabass and implementing selective breeding programs for members of this species complex.